2017
DOI: 10.1590/1807-1929/agriambi.v21n5p344-349
|View full text |Cite
|
Sign up to set email alerts
|

Physical properties of safflower grains. Part I: Geometric and gravimetric characteristics

Abstract: A B S T R A C TSafflower is an oil crop and its oil can be used for food and industrial purposes. However, there is little information about the physical properties of these grains, which is important for the planning and execution of post-harvest stages. Thus, this study was carried out with the aim of evaluating the effect of drying on the main physical properties of safflower grains. Safflower grains were harvested with an initial moisture content of approximately 0.445 decimal d.b. (dry basis) and subjecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
3
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 19 publications
2
3
0
2
Order By: Relevance
“…In other words, drying will increase the ratio of air space volume to the solid volume within the system. This finding is similar to those of Chandrasekar and Viswanathan [34] for coffee; Paksoy and Aydin [54] for squash seeds; Altuntas and Erkol [55] for walnuts and De Souza Smaniotto et al [53] for sunflower seeds, and in contrast to Baryeh [46] for millet and Martins et al [56] for safflower grains who reported ρ b increased with the decrease in MC.…”
Section: Bulk Density True Density and Porositysupporting
confidence: 87%
“…In other words, drying will increase the ratio of air space volume to the solid volume within the system. This finding is similar to those of Chandrasekar and Viswanathan [34] for coffee; Paksoy and Aydin [54] for squash seeds; Altuntas and Erkol [55] for walnuts and De Souza Smaniotto et al [53] for sunflower seeds, and in contrast to Baryeh [46] for millet and Martins et al [56] for safflower grains who reported ρ b increased with the decrease in MC.…”
Section: Bulk Density True Density and Porositysupporting
confidence: 87%
“…As such, a reduction rate of 0.1986 kg in the 1000-grain weight was seen for a one-unit decrease in moisture content (Table 1). Similar results were obtained by Bande et al (2012), Araujo et al (2014), Al-Mahasneh and Rababah (2007) and Martins et al (2017). This phenomenon occurs during drying because the steam pressure in the beans is higher than that of the air, resulting in moisture being removed from the product.…”
Section: Contentssupporting
confidence: 80%
“…A dureza do tegumento/pericarpo e a formação de espaços vazios no interior das sementes têm sido apontadas como as principais causas da redução da massa específica aparente e real apresentada por sementes de algumas espécies durante a secagem (ARAUJO et al, 2014;GONÇALVES et al, 2014;MARTINS et al, 2017b). Araujo et al 2014 Na Figura 7 é possível constatar que a redução do teor de água das sementes promoveu o decréscimo da porosidade intergranular, reduzindo linearmente de 41,8 para 24,8% entre 0,4746 a 0,1124 b.s.…”
Section: Figuraunclassified